ANTHOCYANINS IN THE COBS AND EXTRACTS OF PURPLE CORN (Zea Mays L) “INIA 615” PRESERVED UNDER SHELF - Cerro Ruiz, Samuel (2021)
Anthocyanins were identified and quantified by UPLC in purple corn cobs (Zea mays L), also called “INIA 615” or “Negro Canaán”, and their extracts were preserved in glass containers on a shelf. The differentiated pH method and 3x2^2 Mixed Factorial Design with 14 fact treatments were applied to total anthocyanins using the Statgraphics Centurion XVII for statistical analysis and taking into account the degradation of total anthocyanins as the dependent variable as well as the following independent variables: a) storage/samplingtime: 15, 52, and 90 days; b) amber, green, and colorless containers with permanent lighting of 470 lux/m2; and c) pH 3, 3.5, and 4. In crowns, 12.98 mg/g of total anthocyanins were found, including 4.94 mg/g of cyanidin-3-glucoside, and 3.38 mg/g of cyanidin-3-(6''- malonylglucoside). Extracts mostly contained 93.56 μg/mL of cyanidin-3-glucoside, and 48.15 μg/mL of cyanidin-3-(6''-malonylglucoside). Variables had a significance level of p < 0.05. At 90 days, both cyanidins were degraded: cyanidin-3-glucoside (69.63%, amber, pH 3; 79.05%, colorless, pH 4), and of cyanidin-3-(6''-malonylglucoside) (91.61%, amber, pH 3; 95.35%, colorless, pH 4).